A Glass Numismatic Weight (Exagion) with a Depiction of St. Nicholas - ΣΙΝΑΚΟΣ Αναστάσιος (Byzantina Symmeikta, 2018)
In the Museum of Byzantine Culture a glass numismatic weight (exagion) is kept. A bust of a bearded male figure, with a halo around his head, is depicted on the object. The bust is accompanied by an inscription on its both sides, which goes as follows: | ΝΙ | Κ, – Ο | Λ | Α, : ὁ ἅ(γιος) Νικόλα(ος). The saint is wearing the omophorion above phelonion, while he holds a book, probably the Gospel, with his left hand. Due to the depiction it carries, this exagion is unique. Research on this kind of objects is not aware of exagia with representations of saints. There are only exagia which carry the depiction of the bust of Christ. This weight can be dated to the end of 5th – mid-7th c. and it carries one of the oldest depictions of saint Nicholas. It is most probably connected to the eparch Nicholaos, who issued a lead seal with the depiction of saint Nicholas, published by Zacos-Veglery and dated to the 7th c., or to another eparch, with the same name. Of course,it is important to emphasize that only a future physicochemical examination of the composition of its material and a comparison with the composition of other weights will fully enlighten the question of its dating. If it is proved by this method that it does not belong to the first Byzantine era, then it is possible that this is a commemorative object from a pilgrimage of saint Nicholas.